ANALISIS DESKRIPTIF KECURANGAN YANG DILAKUKAN MAHASISWA DALAM PERTANGGUNG JAWABAN PENGGUNAAN DANA KEGIATAN MAHASISWA (DALAM KERANGKA TEORI FRAUD - Aisyah Assadiah Putri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to explain the process of accountability report preparation of student activity funds and explain factors that affect student’s decision to commit acts of fraud in reporting the use of their funds. This research was conducted on students of Faculty